Energy-efficient two-stage chain protocol routing algorithm for wireless sensor networks - Farhan, Husam Kareem (2014)
Wireless sensor nodes are mostly used in extreme environments, especially at remote and hostile areas including battlefield, volcanoes and underwater. Thus, it is difficult to replenish the energy source of the sensor node once it is installed. One of the factors that plays very important role in extending the wireless sensor networks lifetime is routing algorithm. In order to extend the lifetime of the nodes, we propose a new routing algorithm that can achieve significant energy conservation in WSNs, known as Two Stage Chain Routing Protocol (TSCP). The main objective of TSCP is to increase the network lifetime of wireless sensor networks. The new TSCP routing algorithm is compared with other similar grid-based routing algorithms namely Chain-Cluster based Mixed routing (CCM) and Chain-Chain Based Routing Protocol (CCBRP). TSCP algorithm divides the sensor network into multiple chains and work within two stages. The first stage is dividing the nodes to horizontal chains that include all sensor nodes within the same row and one of the nodes in the chain will act as a head for other members. The second stage is involving the formation of vertical chain that includes all chain heads, one of the nodes in the vertical chain that includes all chain heads and selecting one of the nodes to act as a main head for the entire network. Simulation results show that TSCP algorithm outperforms CCM and CCBRP algorithms in terms of four performance metrics namely Network lifetime, FND and LND (First Node and Last Node Died), network stability period, and energy consumption. The main concern for TSCP algorithm is to extend the lifetime of wireless sensor network. As a result, TSCP could achieve an improvement over CCM and CCBRP algorithms in about 25% and 8% respectively for small network size (3 X 3) sensor nodes configuration. At the same time, TSCP could achieve about 29% and 9% improvement in comparison with CCM and CCBRP respectively using medium network size, (9 X 9) sensor nodes configuration. When we carried on the comparison using large network size, which is (15 X 15) sensor nodes configuration, TSCP shows an improvement about 25% and 18% over CCM and CCBRP algorithms respectively.